Pemberdayaan DUIT:: Signifikansi Kepemimpinan Partisipatif Dalam Pemberdayaan Jemaat di Masa PPKM Pandemi Covid-19 - Kawangmani, Soleman; Harjanto, Hery (IAKN TORAJA, 2022)
Abstract: The Covid-19 pandemic has hampered the ministry of church leaders to the congregation, including when implementing the PPKM policy. Mutual attention between congregations is also reduced. However, the emergence of the